Solar Energy Based Smart Irrigation System using IoT - R, Kathiresan; M, Janani; M, Naveen K; E, Narashimabalaji; R, Rasiga (Journal of ISMAC, 2023)
This paper proposes a solar-based smart irrigation system that utilizes Internet of Things (IoT) technology to automate irrigation in agriculture. Traditional irrigation systems can lead to over-watering or under-watering of crops, which can result in reduced crop yield and wastage of water resources. Additionally, they often require significant energy costs to operate and can waste significant amounts of water through evaporation, runoff, and inefficient distribution. These systems also offer limited monitoring and control capabilities, requiring farmers to physically inspect their fields to ensure that the irrigation system is functioning correctly. However, a solar energy smart irrigation system using IoT can overcome these issues by continuously monitoring soil moisture levels, optimizing water usage, and offering remote monitoring and control capabilities. This makes it an ideal solution for farmers looking to maximize their crop production while minimizing their environmental impact. The system includes soil moisture sensors, an Arduino, a solar panel, a water pump, a wireless communication module (Node MCU) and a grid as an alternative source of an energy when there is no sufficient energy from the solar energy. The sensors collect soil moisture, Potassium, sodium and phosphorus data and transmit it to the cloud, which then activates the water pump if the moisture level is below a predetermined threshold. The solar panel provides the necessary power for the system, making it energy-efficient and environmentally friendly. The system also allows for remote monitoring and control of irrigation through a mobile application or a web-based interface. The proposed system offers a cost-effective, sustainable, and efficient solution to irrigation in agriculture, with the potential to increase crop yields while conserving water resources using IoT technologies to automate and optimize irrigation practices in agriculture. The system utilizes soil moisture sensors, Potassium, sodium and phosphorus sensors, and amount of water needed for crops. The system is designed to be energy-efficient, cost-effective, and easy to use. It can be remotely controlled and monitored via a mobile application, allowing farmers to have real-time access to their irrigation systems. This system has the potential to improve crop yields, conserve water resources, and reduce labor costs associated with manual irrigation practices.